A Review of Phycoremediation of Heavy Metals in Industrial Waste Water - Joseph, Ikwebe; David, Bando Christopher; Abershi, Ajiduku Leyoa (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Environmental Pollutants such as heavy metals poised serious threat to biological systems. Heavy metals which could be natural or anthropogenic sourced are non-degradable pollutants and must be eliminated or reduced to certain quantity that is analytically presumed to be a safe limit before discharging into the environment to avoid injurious effects on biological systems. This review work showed the abilities of microalgae to biologically remove heavy metals from waste water through the process known as ‘Phycoremediation’. Phycoremediation of heavy metals with the help of microalgae takes place in two stages: Biosorption and Bioaccumulation. Microalgae such as Nannochloropsis oculata, Scenedesmus sp, Scenedesmus obtusus, Gracilaria corticata, Sarcodia suidae and Spirulina sp has been proven to phycoremediate; Pb, Cr, Hg, As, Cd, and Cu respectively. Therefore, this review work has shown that the microalgae are efficient biological vectors for heavy metal uptake.